PEMBELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH NEGERI SIMPANG NUNGKI KECAMATAN CERBON KABUPATEN BATOLA - Ria Susanti (ADIBA : JOURNAL OF EDUCATION, 2022)
This study aims to describe how the theory and practice of learning the Akidah Akhlak subject at Madrasah Ibtidaiyah Negeri Simpang Nungki Kec. Cerbon Kab. Batola, South Kalimantan, specifically for grades IV, V, and VI. By using the type of field research (field research) and descriptive qualitative approach, as well as with the techniques of observation, interviews, and documentation for data collection. The results of the study show that the learning of Akidah Akhlak in MIN Simpang Nungki, Cerbon District, Barito Kuala Regency. South Kalimantan, grades IV, V and VI which have been running very well overall. Because the learning components used are complete and in accordance with teaching and learning theory. Such as the use of varied learning methods and strategies (lectures, discussions in the form of the educational-diagnosis meeting, question-and-answer, demonstrations and assignments), the use of interesting teaching aids/media and following IT developments (pictures & LCD), the competence of the teacher is also is in accordance with the educational qualifications as an educator of the Akidah Akhlak subject. And this madrasah has implemented the 2013 curriculum in learning.This article is very useful as an analysis of the development of learning theory and practice in the Islamic Religious Education curriculum